Evaluacion de bacterias Gram positivas presentes en heces de porcinos de la provincia de Zamora Chinchipe - Allasiche Cango, Santos Alcivar (2025)
The intestinal microbiota significantly influences animal health by participating in multiple physiological functions. In recent years, pig farms have made significant advancements in production to improve their status. However, digestive disorders associated with microbiota imbalances, known as dysbiosis, have gained particular importance in pig production. Therefore, an evaluation of Gram-positive bacteria present in pig feces was conducted in 35 farms in the province of Zamora Chinchipe. A higher prevalence was observed in traditional farming systems, which use balanced feed and antibiotics. Identified bacteria included Bacillus spp., Micrococcus spp., Staphylococcus aureus, coagulase-negative Staphylococcus, and Streptococcus spp. The Lactobacillus spp. count averaged between 7.21×1011 and 1012 CFU/ml across all categories. An association between the presence of Bacillus spp. and the farming system was observed. The dendrogram analysis revealed four distinct groups with similar characteristics. Although these microorganisms can be beneficial, their uncontrolled proliferation may become pathogenic. Factors such as age, diet, stress, hygiene, and environment can influence this imbalance, affecting both the health and performance of pigs.